Measurements of linear polarization of satellite transitions from Li- and Be-like Ar ions. (18th June 2020) - Gall, A C; Dipti,; Buechele, S W; Sanders, S; Szabo, C I; Silwal, R; Ralchenko, Yu; Brickhouse, N; Takacs, E
Abstract: Non-thermal electron distributions, such as beams of electrons, are found in many laboratory and astrophysical plasma sources and can produce anisotropic and polarized emission. Theories used to model the emission require sublevel specific analysis, which can be difficult to verify experimentally. Using two polarization-sensitive Johann-type crystal spectrometers at the National Institute of Standards and Technology (NIST) electron beam ion trap facility, we measured the linear polarization of well-known dielectronic recombination satellite transitions from Li-like Ar ions and two blended features from Be-like ions. The spectrometers observed the plasma at 90° relative to the electron beam propagation direction, and the crystal dispersion planes were oriented perpendicular relative to each other to allow for differing polarization sensitivities. Measurements were taken near the resonance energies of each line and compared with theoretical predictions based on relativistic magnetic sublevel atomic kinetics using the density-matrix theory. Most of the predictions are in excellent agreement with measured values.